Controle de corrente aplicado a conversores PWM conectados à rede elétrica sem sensor de tensão CA utilizando observadores de corrente por modos deslizantes - Tonin, Rodrigo Gehrke (2014)
This master thesis presents a current sliding mode observer for voltage sensorless grid connected converters. To perform the grid synchronization a sliding mode current observer in stationary axes αβ is proposed. Aiming its implementation in digital signal processors or microcontroller both the synchronism and control are developed in discrete time domain. Firstly the line currents are measured, then the transformation to stationary axes is carried out and the sliding mode current observer is proposed. Based on a Fortescue discrete component theory an algorithm to separation of sequence positive phase is proposed aiming to obtained the positive grid angular position to realized the synchronous coordinates axes transformation. The current control is carried out by two PI controllers designed in a discrete time domain. The good performance of the proposed method is proven through the simulation and experimental results.